Hipersuperfícies com r-ésima curvatura média constante positiva em Mm X R - Pinheiro, Antônia Jocivania (2010)
In this paper, we define the transformations of Newton and prove some properties related to them. We did a study on elliptic operator and use it to prove that given some conditions for the sectional curvature of a riemannian manifold M,able function of increasing height (in modulus) of a graph vertical compact immersed in MXR.